Analysis Of The Impact Of Financial Technology On Employee Performance at PT. Bsi Tbk Gunung Tua Brand Office - Arif, Muhammad; Amri, Khoirul; Susanti, Rika (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The discussion of this research relates to the field of computer banking and human resource management. The theory used in this study is the theory of Islamic finance, the theory of finance, the theory of technology and the theory of performance. Fintech is a technological innovation developed in the financial sector that is able to replace the role of formal financial institutions such as banks with a payment system that provides a market for business actors.This research is a qualitative research with a descriptive approach. Data collection techniques used are observation techniques, interviews and documentation. Sources of data used are primary data and secondary data. The number of informants is 10 employees at PT. Bank Syariah Indonesia, Tbk Gunung Tua Sub-Branch Office.The results of this study are that the presence of financial technology (fintech) has an impact in increasing the work of each employee at PT. Bank Syariah Indonesia, Tbk Gunung Tua Sub-Branch Office. Financial technology (fintech) has a positive impact on employee performance in completing work. Fintech makes interactions between employees and customers easier and can be done anytime and anywhere without having to take a long time. Keywords: Financial Technology (Fintech), Employees, Performance.